Health Outcomes Associated with Mild vs. Moderate-to-Severe Laboratory-Confirmed Influenza in 6- to 35-Month-Old Children. (4th October 2017) - Hsiao, Amber; Buck, Philip O; Yee, Arnold; Hansen, John; Lewis, Ned; Yanni, Emad; Bekkat-Berkani, Rafik; Nelson, Deborah; Schuind, Anne; Klein, Nicola P
Abstract: Background: In children <5 years old, influenza is associated with high-risk of serious disease and hospitalization. Non-US data suggest that a moderate-to-severe (M-S) influenza disease classification may be clinically significant. A Finnish study found that 2/3 of young children had M-S influenza, with most presenting with acute otitis media (AOM) and/or fever >39°C; high rates of antibiotic use were associated with M-S influenza. No data regarding this M-S definition in US children exists. We assessed differences in health outcomes between children with M-S vs. mild laboratory-confirmed influenza disease within Kaiser Permanente Northern California (KPNC), a large integrated healthcare delivery system. Methods: All KPNC members ≥6 months to <36 months old who had a positive polymerase chain reaction (PCR) test for influenza A or B during the 2013–14 influenza season. We classified as M-S influenza cases those with ≥1 of the following: fever >39°C, AOM, lower respiratory tract infection (LRTI) or extra-pulmonary complications (e.g., seizure); cases with none were classified as mild influenza. Comparing M-S vs. mild influenza, we estimated the risk ratio of having ≥1 hospitalization, being admitted to intensive care unit (ICU) and receiving antibiotics/antivirals ≤14 days following the PCR test. We used χ 2 to calculate P values. Results: Of the 293 influenza-positive children in the study, 189 (65%) were classified as M-S and 104 (35%) as mild. Among M-S cases, the most common symptoms were LRTI (64%), fever (43%) and AOM (28%). Few had extra-pulmonary complications (9%). M-S cases were 9 times more likely to receive antibiotics compared with mild cases (95% confidence intervals: 4.1–19.8; P < 0.01); there was no significant difference in antiviral receipt. Few children overall were hospitalized (5%) or admitted to the ICU (1%). Conclusion: Among US children aged 6–35 months, most had M-S influenza; this was associated with a 9-fold increased risk of receiving antibiotics. The proportion of children presenting with M-S influenza was similar to that of non-US cohorts, but the most common symptom here was LRTI. Additional work is needed to evaluate the utility of clinical severity definitions among young children with influenza. Funding: GSK (HO-16-17304) Disclosures: A. Hsiao, Kaiser Permanente Vaccine Study Center: Employee, Salary; P. O. Buck, GSK: Employee and Shareholder, GSK stock options or restricted shares and Salary; A. Yee, Kaiser Permanente Vaccine Study Center: Employee, Salary; J. Hansen, Kaiser Permanente Vaccine Study Center: Employee, Salary; N. Lewis, Kaiser Permanente Vaccine Study Center: Employee, Salary; E. Yanni, GSK: Employee, Salary; R. Bekkat-Berkani, GSK: Employee, Salary; A. Schuind, GSK: Employee and Shareholder, GSK stock options or restricted shares and Salary; N. P. Klein, GSK: Investigator, Grant recipient; sanofi pasteur: Investigator, Grant recipient; Merck & Co.: Investigator, Grant recipient; MedImmune: Investigator, Grant recipient; Protein Science: Investigator, Grant recipient; Pfizer: Investigator, Grant recipient